Industrial training report: Penang Adventist Hospital / Nurul Athirah Azhar Laile - Azhar Laile, Nurul Athirah (Universiti Teknologi MARA, Perlis, 2024)
The primary topic of this internship report is the job experience I gained throughout my sixmonth industrial training at Penang Adventist Hospital. This report highlights my internship experience at this hospital, namely in the areas of human resources, and that involves recruitment. While working on my internship here, I experienced both intrinsic and extrinsic rewards. At Penang Adventist Hospital, I will need apply all of the skills and knowledge I gained while studying at Universiti Teknologi Mara (UiTM) Arau, Perlis in Bachelor of Business Administration (Hons.) Human Resource Management. The purpose of this report is to identify and comprehend the organization's internal strengths and weaknesses, as well as external opportunities and threats. The SWOT matrix of an organization will be effective in identifying and improving weaknesses. SWOT analysis is critical for them to evaluate their difficulties and strengths in order to be listed among the healthcare field. This research is going to look at the advantages of chances, how to overcome weaknesses, and how to avoid threats.